Penerapan Model Science, Environment, Technology, And Society (SETS) Berbantuan Video Pada Materi Ekosistem Terhadap Sikap Peduli Lingkungan Kelas VIII SMP Bustanul Ulum - hamdan atun; Mustika Sari; Herditiya Herditiya (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
Abstract: This study aimed to determine the effect of the Science, Environment, Technology, and Society (SETS) learning model assisted by instructional videos on the environmental care attitude of eighth-grade students at SMP Bustanul Ulum Lintang Batang in the ecosystem topic. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 15 students selected through total sampling. Data were collected using an environmental care attitude questionnaire, observation sheets, and pretest-posttest instruments. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed Rank Test because the data were not normally distributed. The results showed that the average percentage of students' environmental care attitude after the implementation of the SETS learning model assisted by instructional videos reached *84.40%, which falls into the **very good* category. However, the Wilcoxon Signed Rank Test yielded an Asymp. Sig. (2-tailed) value of *0.506* (>0.05), indicating that there was no statistically significant difference between the pretest and posttest scores. Therefore, the implementation of the SETS learning model assisted by instructional videos did not have a significant effect on students' environmental care attitude, although descriptively it showed an improvement toward a better level of environmental awareness. Keywords: SETS learning model, instructional video, environmental care attitude, ecosystem, science education.